IGPR-1 Is Required for Endothelial Cell–Cell Adhesion and Barrier Function. Issue 24 (4th December 2016) - Wang, Yun Hwa Walter; Meyer, Rosana D; Bondzie, Philip A; Jiang, Yan; Rahimi, Ida; Rezazadeh, Kobra; Mehta, Manisha; Laver, Nora M.V.; Costello, Catherine E.; Rahimi, Nader
Abstract: Endothelial cell (EC) barrier function plays a prevalent regulatory mechanism for the integrity and homeostasis of blood vessels and modulates angiogenesis and immune responses. Cell adhesion molecules (CAMs) play a central role in the barrier function of ECs. Although Ig-containing and proline-rich receptor-1(IGPR-1) was recently identified as a novel CAM expressed in ECs, the molecular mechanisms underlying the function of IGPR-1 in ECs remain uncharacterized. In this report, we investigated the role of IGPR-1 in EC barrier function and the molecular mechanism of its activation in ECs. We demonstrate that IGPR-1 is localized to endothelial adherens junctions and, through trans -homophilic dimerization, regulates endothelial cell–cell adhesion and barrier function. Trans -homophilic dimerization of IGPR-1 stimulates the phosphorylation of serine 220 (Ser220), which is required for IGPR-1 to regulate endothelial barrier function and angiogenesis. Moreover, IGPR-1 chimera, which mimics the trans -homophilic dimerization of IGPR-1, induced a sustained phosphorylation of Ser220 upon stimulation with a ligand. Coordinated dimerization of IGPR-1 and its homophilic interaction modulates its adhesive function and Ser220 phosphorylation. This adhesive function of IGPR-1 contributes to the barrier function of ECs. Graphical Abstract: Highlights: Molecular mechanisms of endothelial cell–cell adhesion and barrier function are not fully understood. IGPR-1 is a novel CAM expressed in ECs and is localized to endothelial adherens junctions. IGPR-1through trans -homophilic dimerization regulates endothelial cell–cell adhesion and barrier. Trans -homophilic dimerization of IGPR-1 stimulates the phosphorylation of Ser220, which is required for IGPR-1 to stimulate endothelial barrier function and angiogenesis.